The Concept of Digital Money in Islamic Economic Perspective: Case Study of GoPay Digital Money Application - Fata, Zainol (Ta'amul: Journal of Islamic Economics, 2022)
Money is one of the most Important elements in transaction activities, this is because money can facilitate the transaction process along with the times and technology, community activities in conducting transactions have started using technology, namely digital money. His study focuses on the problem of how the Islamic economic view of digital money transaction tools is a case study of the GoPay digital money application. The researcher uses a qualitative approach, this type of research is descriptive, namely the data collected in the form of words and not numbers. In the research that has been done, the findings are based on the focus of the research, namely how Islam views digital money transactions. The use of digital money in transactions is allowed for good purposes.